Metaverse as a possible tool for reshaping schema modes in treating personality disorders - Yin, Bin; Wang, Ya-Xin; Fei, Cheng-Yang; Jiang, Ke (Frontiers in Psychology, 2022)
Personality disorders are usually treated with face-to-face sessions and/or digital mental health services. Among many genres of therapies, schema therapy stands out because rather than simply targeting the symptoms of PD, it cordially targets the cause of PD and heals the early maladaptive schema, thus is exceptionally good at soothing emotional disturbances before enacting cognitive restructuring, resulting in long-term efficacy. However, according to Piaget’s genetic epistemology, the unmet needs lie in the fact that the cognitive structure (i.e. schema) that determines the adaptive behavior can only be formed in the interaction with the real world that the patient is living in and reinforced by the feedback from the object world upon the patient’s newly-formed behavior. Therefore, in order to reshape the patient’s schema modes to support adaptive behavior and regain emotional regulation capabilities of the healthy adult, one may have to reconstruct the object world surrounding the patient. Metaverse, the bestowed successor to the Internet with the cardinal feature of “the sense of full presence”, can become a powerful tool to reconstruct a new object world for the patient with the prescription of a psychotherapist, so as to transform the treatment techniques in schema therapy into the natural autobiographical experiences of patients in the new object world, thus gradually reshape the patient’s schema modes that can ultimately result in an adaptive, and more inclusive, interaction with the real world. This work describes the underlying theory, the mechanism, the process and ethical considerations of such promising technology for the not-too-far future.